Jax Freeman and the tournament of spirits - Mbalia, Kwame (Mbalia, Kwame. Jax Freeman, 2025)
The story follows a seventh-grade student who has recently learned that he can summon ancestral magical abilities. After completing initial training, he and several classmates participate in an international competition for summoners. During the event, he is assigned an additional task to observe other competitors in order to identify who is responsible for releasing dangerous cryptids into the tournament setting. As he navigates the challenges of the competition, he must balance his responsibilities, protect his peers, and confront an unknown threat. The narrative explores themes of teamwork, loyalty, and the use of magical powers within an action-oriented fantasy framework.